Chapter 13: Drivers and barriers for industrial symbiosis: the case of Mo Industrial Park - Jakobsen, Siri (Edward Elgar Publishing, 2021)
Innovation is a key enabler for industrial symbiosis (IS) between actors in a system, in which the waste from one actor can be used as input in another actor's production and thereby create mutual benefits for each actor and the system as a whole. However, developing IS might be challenging for firms, as it requires capital investments, regulatory incentives and cooperation. To increase our knowledge of the development of IS, this chapter identifies IS drivers and barriers between firms in Mo Industrial Park over the course of a decade. We find that developing a circular industry is a long-term process that requires open innovation efforts where academic institutions are essential in mobilizing firms towards circularity. The main barrier for IS development, both in 2010 and 2020, is the economy, where firms lack access to risk capital to invest in research-based circular solutions. Due to limited research and development (R & D) and innovation experience, firms also experience an initiative overload where they find it challenging to choose relevant initiatives in which to invest resources.